Management of High Cardiovascular Risk in Diabetic Patients: Focus on Low Density Lipoprotein Cholesterol and Appropriate Drug Use in General Practice - Rottura, Michelangelo; Scondotto, Giulia; Barbieri, Maria Antonietta; Sorbara, Emanuela Elisa; Nasso, Chiara; Marino, Sebastiano; Scoglio, Riccardo; Mandraffino, Giuseppe; Pallio, Giovanni; Irrera, Natasha; Imbalzano, Egidio; Squadrito, Giovanni; et al. (Frontiers in Cardiovascular Medicine, 2021)
This study aimed to evaluate the management of high cardiovascular risk (CVr) in the patients with diabetes by exploring the prescribing behavior in a setting of general practitioners (GPs). A retrospective cohort study was carried out using the data recorded between 2018 and 2020 in the clinical database of 10 GPs. Diabetes was defined using the International Classification of Diseases (ICD-9-CM) coding (250*) or using the laboratory parameters (hyperglycemia condition: ≥126 mg/dL). A cohort was described stratifying by demographic, clinical and therapeutic characteristics, and laboratory tests. Both the CVr and statin prescriptions were evaluated; adherence to statin therapy (medication possession ratio, MPR ≥ 80) was calculated in accordance with the low-density lipoprotein cholesterol (LDL-C) target. The multivariate logistic regression models with adjusted odds ratios (ORs) and the corresponding 95% Confidence Intervals (CIs) were calculated to identify the predictors of lipid modifying agents use and achieved target therapy; moreover, glucose-lowering drugs use was evaluated. Out of 13,206 people screened, 1,851 (14.0%) patients were affected by diabetes mellitus (DM), and 1,373 were identified at high/very high CVr. Of them, 1,158 (84.3%) had at least one measurement of LDL-C, and 808 (58.8%) received a prescription with at least one lipid-lowering drug (LLD). The patients at high/very high CVr treated or not treated with LLD, reached the LDL-C target in 24.0 and 10.3%, respectively (p < 0.001). Furthermore, 34.6% of patients treated with high intensity LLDs and adherent to therapy showed the LDL-C values below the therapeutic target. Out of 1,373 patients at high/very high CVr, 958 (69.8%) had at least one prescription of glucose-lowering drugs. Of them, 52.0% (n = 498) were prescribed not in agreement with the current guidelines. More specifically, 392 patients (40.9%) were treated with metformin only, while the remaining 106 (11.1%) were treated with metformin together with hypoglycemic agents other than glucagon-like peptide-1 receptor agonists (GLP1-RA) or sodium-glucose-transporter 2 (SGLT2) inhibitors. Our results suggest the urgent need to improve the management of patients with diabetes at high and very high CVr in the real life, to reduce the burden of diabetes on the health system.